Non-coding RNAs in Rheumatoid Arthritis: From Bench to Bedside - Wang, Jinghua; Yan, Shushan; Yang, Jinghan; Lu, Hongying; Xu, Donghua; Wang, Zengyan (Frontiers in Immunology, 2020)
Rheumatoid arthritis is a common systemic and autoimmune disease characterized by symmetrical and inflammatory destruction of distal joints. Its primary pathological characters are synovitis and vasculitis. Accumulating studies have implicated the critical role of non-coding RNAs (ncRNAs) in inflammation and autoimmune regulation, primarily including microRNA (miRNA), long non-coding RNA (lncRNA), and circular RNA (circRNA). NcRNAs are significant regulators in distinct physiological and pathophysiological processes. Many validated non-coding RNAs have been identified as promising biomarkers for the diagnosis and treatment of RA. This review will shed some light on RA pathogenesis and be helpful for identifying potential ncRNA biomarkers for RA.